Effectiveness of Led Photobiomodulation Therapy on Treatment With Knee Osteoarthritis: A Rat Study. (August 2020) - Trevisan, Eduardo Santos; Martignago, Cintia Cristina Santi; Assis, Livia; Tarocco, Juliana Carolina; Salman, Soraia; dos Santos, Laurita; Liebano, Richard; Tim, Carla Roberta
Abstract : Objective: The present study aimed to evaluate the effectiveness of photobiomodulation therapy by light-emitting diode on osteoarthritis treatment in the knees of rats. Design: Twenty male Wistar rats were randomly assigned into two experimental groups: OAC: animals subjected to induction of osteoarthritis, without therapeutic intervention and the group OAL: animals subjected to induction of osteoarthritis treated with light-emitting diode photobiomodulation therapy (850 nm, 200 mW, 6 J). Results: The results of gait analysis showed no statistical difference between the groups. The histological findings showed that the OAL group presented abnormal chondrocyte orientation, yet with less irregularities along fibrillation and the joint tissue. Thus, it presented a lower degenerative process when evaluated by the Osteoarthritis Research Society International. Likewise, in the immunohistochemical analysis, the OAL group showed higher collagen 2 and transforming growth factor β immunoexpression when compared with the OAC group. Conclusions: Given the above, it is possible to suggest that the photobiomodulation therapy by light-emitting diode had positive effects on the expression of extracellular matrix proteins responsible for synthesis of articular tissue.